Three essays on environmental Engel curves and international trade - Li, Ailun (Kansas State University, 2024)
This dissertation comprises three chapters that investigate the correlation between household consumption choices and environmental consequences in the context of evolving after-tax incomes, with a specific focus on foreign content. Utilizing Engel curves, we analyze this relationship and subsequently decompose the composition effect to further estimate the contributions of changing consumption patterns. In the first chapter, we estimate Engel curves to analyze the influence of foreign content (outsourcing) and foreign environmental taxes embedded in the consumption of final goods and services in the United States (U.S.). Using U.S. household income and consumption data spanning from 1996 to 2011, we observe that Engel curves exhibit concave shapes, gradually shifting downward over time in relation to the foreign content of goods and upward in response to foreign environmental taxes. Our findings indicate a decrease in the foreign content of U.S. household consumption bundles over time, primarily driven by significant income growth, leading to a shift in consumption towards goods with higher domestic content. This shift represents a movement along the Engel curve. Conversely, the greater share of U.S. household consumption of goods utilizing foreign inputs sourced from countries with higher environmental taxes is attributed to factors beyond income. Consequently, these factors contribute to the upward shift in this Engel curve. In the second chapter, we examine the role of household consumption decisions in the generation of industrial waste and dust emissions. This inquiry stems from the association between manufacturing activities and environmental concerns, particularly regarding industrial waste and dust. Despite recent comprehensive policies in China effectively reducing emissions of atmospheric pollutants such as SO2, NOx, CO, PM10, and VOC, industrial waste and dust remain significant issues in Chinese metropolitan areas. Employing environmental Engel curves, we explore this relationship over time. Our findings indicate that Chinese households have contributed to lower industrial waste and dust emissions over time, primarily due to changes in the relative supply and demand of pollution-intensive goods. This shift is reflected in a change in the Engel curve, accounting for 76% of the decline in industrial waste and dust emissions embedded in the consumption of goods in China. In the third chapter, we conduct a systematic examination of Environmental Engel curves (EECs) to discern disparities between developed and developing countries based on their respective environmental stringency levels. Recognizing the substantial variability in environmental regulatory frameworks across nations, our empirical findings reveal that developing nations significantly contribute to the pollution embedded within U.S. household consumption patterns. This finding contrasts with the fact that developed countries primarily serve as the leading trade partners of the United States of America. Additionally, our study finds that pollution levels would have decreased over time, even without changes to production techniques. This decline can be attributed roughly equally to two trends: household income growth, reflected by movements along inelastic EECs, and economy-wide changes represented by downward shifts in EECs over time.
Keywords: International trade